Enhancing Fiqh Learning Achievement Through the Demonstration Method: A Case Study in An Indonesian Islamic Elementary School - Dewi, Rachma Rusdiana; Fatimah, Meti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The participants consisted of one Fiqh teacher and twenty-eight second-grade students, observed over a three-month period of classroom learning. study aims to describe the application of the demonstration method in Islamic jurisprudence (fiqh) learning and analyse its impact on the learning achievement of second-grade students at Al Akbar Pandeyan Elementary School. This study used a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. Data analysis followed the Miles & Huberman model. The results showed that the demonstration method was implemented systematically through material explanations, direct demonstrations by teachers, and student practical guidance, supported by simple, relevant learning media. The application of this method improved students' conceptual understanding, practical worship skills, active participation, motivation, and self-confidence. Significantly, the majority of students achieved or exceeded the learning objective achievement criteria. Thus, the demonstration method has proven effective in improving the quality of Islamic jurisprudence learning at Al Akbar Pandeyan Elementary School, particularly in materials requiring mastery of practical skills.